Preparation method of long-time fireproof and heat-insulating aluminum oxide-high-entropy ceramic filled sponge, aluminum oxide-high-entropy ceramic filled sponge and application of aluminum oxide-high-entropy ceramic filled sponge

The alumina-high entropy ceramic filled sponge addresses the limitations of existing materials by combining alumina fiber with a high entropy ceramic core for enhanced protection and comfort, ensuring safety and ease of preparation.

CN119217741APending Publication Date: 2024-12-31ZHEJIANG ROUHE NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411337216.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing firefighting materials face challenges such as limited protection in extreme high temperatures, complex preparation processes, high costs, and reduced long-term protective performance due to poor flexibility and deformability.

Method used

A method to prepare a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge by combining alumina fiber with a high entropy ceramic fiber core layer, using sol-gel and electrospinning processes to create a sandwich structure, followed by hot pressing, which avoids high-temperature calcination.

Benefits of technology

The sponge provides excellent fireproofing and heat insulation, maintains deformability for comfort, and ensures safety under extreme conditions while simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217741A_ABST
    Figure CN119217741A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of long-time fireproof heat-insulation aluminum oxide-high-entropy ceramic filled sponge, the aluminum oxide-high-entropy ceramic filled sponge and application of the aluminum oxide-high-entropy ceramic filled sponge, and belongs to the field of firefighter uniform. The preparation method comprises the following steps that S1, a high-entropy ceramic nanofiber core layer is prepared; s2, preparing an inorganic mixed spinning solution or an organic mixed spinning solution; s3, spinning alumina fiber surface layers on two sides of the high-entropy ceramic nanofiber core layer by adopting an electrostatic spinning process to obtain an alumina fiber surface layer-high-entropy ceramic nanofiber core layer-alumina fiber surface layer foam material with a sandwich structure; and S4, performing hot press molding to obtain the aluminum oxide-high-entropy ceramic filled sponge. According to the preparation method of the long-time fireproof and heat-insulating aluminum oxide-high-entropy ceramic filled sponge, the aluminum oxide-high-entropy ceramic filled sponge and the application thereof, the flexibility of the aluminum oxide fibers and the ultrahigh temperature resistance of the high-entropy ceramic fibers are combined, so that the working safety and wearing comfort of firefighter uniform are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of firefighting clothing, and in particular to a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filling sponge, an alumina-high entropy ceramic filling sponge and applications thereof. Background Art

[0002] Firefighters face multiple dangers such as high temperature, flames and smoke when performing their duties, so the design and performance of their safety equipment are crucial. Alumina fiber sponge can usually withstand high temperatures of 1000°C. Although it can provide a certain degree of protection, its protective effect may be limited in the face of extreme high temperatures and long-term exposure to fire environments.

[0003] In recent years, high entropy ceramic fiber sponge has attracted much attention as a new type of high-temperature resistant material. The disorder of its structure gives it the advantages of low thermal conductivity, high radiation thermal impedance and strong wear resistance. It can withstand high temperatures of 1000℃-2000℃, so it has a very broad application prospect in fire suits. However, its poor flexibility and deformability affect the work safety and comfort of firefighters.

[0004] At the same time, the existing related insulation materials research is as follows:

[0005] CN202311496915.1 discloses a silica-loaded porous alumina nanofiber flexible material and a preparation method and application thereof, wherein an aluminum source, a porogen, a high molecular polymer and an organic solvent are mixed and stirred and ultrasonically treated to obtain a sol-gel spinning solution, which is used to electrospin to obtain an aluminum precursor / polymer fiber film and calcine to obtain a porous carbon nanofiber film of alumina fiber with a mullite structure, which is infiltrated into a hydrothermal solution containing a silicon source for hydrothermal reaction, a hydrothermal product is obtained, and washed, dried and calcined in sequence to obtain a silica-loaded porous alumina nanofiber flexible material. It can be used as a fireproof and heat-insulating material, but since the preparation process requires hydrothermal, there are problems such as a complicated operation process and certain experimental dangers.

[0006] CN202310878724.5 discloses a flexible high temperature resistant heat insulating sheath and its preparation method, which uses heat insulating heat resistant inorganic fiber and powder as the inner layer filling, or requires high silica cloth + polycrystalline alumina fiber cloth composite. Since it needs to obtain composite refractory cloth by stacking and sewing multiple refractory cloths, there are problems such as complex preparation process and high cost.

[0007] CN202211539139.4 discloses a multifunctional protective and energy-saving efficiency-enhancing coating and its preparation method, which uses spinel high-entropy ceramics and rare earth oxides as the main raw materials of the coating to synergistically increase the high-temperature corrosion resistance of the protective layer. However, it requires high-temperature calcination, and the coating may wear, fade or peel off over time, greatly reducing its long-term protective performance. Summary of the invention

[0008] To solve the above problems, the present invention provides a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge, an alumina-high entropy ceramic filled sponge and its application, which combines the flexibility of alumina fiber with the ultra-high temperature resistance of high entropy ceramic fiber to take into account the work safety and wearing comfort of fire suits.

[0009] To achieve the above object, the present invention provides a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge, comprising the following steps:

[0010] S1, preparing a high entropy ceramic nanofiber core layer;

[0011] S11, preparing a precursor sol containing a polymer template, a metal source and a solvent A by a sol-gel method;

[0012] S12, performing electrostatic spinning on the precursor sol to obtain a precursor nanofiber membrane;

[0013] S13, heating the precursor nanofiber membrane, and then calcining it in an air atmosphere to obtain a high entropy ceramic nanofiber core layer;

[0014] S2, preparing an inorganic mixed spinning solution or an organic mixed spinning solution containing an aluminum source, a solvent B and a spinning aid;

[0015] S3, using an electrospinning process based on an inorganic mixed spinning solution or an organic mixed spinning solution, spinning an alumina fiber surface layer on both sides of the high entropy ceramic nanofiber core layer to obtain an alumina fiber surface layer-high entropy ceramic nanofiber core layer-alumina fiber surface layer foam material having a sandwich structure;

[0016] S4. Hot-pressing the alumina fiber surface layer-high entropy ceramic nanofiber core layer-alumina fiber surface layer foam material to obtain an alumina-high entropy ceramic filled sponge.

[0017] Preferably, in step S11, the polymer template is one of polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, polyacrylonitrile and any combination thereof;

[0018] The metal source is one of iron acetate, cobalt acetate, nickel acetate, copper acetate, zinc acetate, manganese acetate, and any combination thereof;

[0019] Solvent A is one of ethanol, N,N-dimethylformamide, methanol, or any combination thereof;

[0020] The weight ratio of the polymer template to the solvent A is 1:2 to 1:30, and the ratio of the total metal content to the solvent A is 1:5 to 1:30.

[0021] Preferably, in step S13, heating is performed in a vacuum oven at 200°C for 2 hours, the calcination temperature is 400°C-1000°C, and the heating rate is 2°C / min-10°C / min.

[0022] Preferably, in step S2, the aluminum source is one of aluminum nitrate nonahydrate, aluminum chloride hexahydrate, aluminum acetate, aluminum sulfate, aluminum isopropoxide, aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum n-butoxide, aluminum sec-butoxide, aluminum tert-butoxide, and any combination thereof;

[0023] Solvent B is one of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, n-pentanol, ethylene glycol, butanediol, hexanediol or glycerol, or any combination thereof;

[0024] The spinning aid is one of polyacrylamide, polyvinyl pyrrolidone, hydrolyzed polyacrylamide, polyacrylic acid and its salt, polyvinyl alcohol, polyoxyethylene and any combination thereof;

[0025] The ratio of aluminum source, solvent B and spinning aid is 10-30:50-130:0.5-5.

[0026] Preferably, in step S4, the hot pressing temperature is 20°C-400°C, the time is 1 min-20 min, and the pressure is 1 kPa-1000 kPa.

[0027] The alumina-high entropy ceramic filling sponge is prepared by the method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filling sponge.

[0028] The application of the alumina-high entropy ceramic filled sponge in firefighting clothing.

[0029] The present invention has the following beneficial effects:

[0030] 1. Excellent fireproofing and heat insulation and wear resistance: Based on the alumina fiber that can withstand 1000℃, it is compounded with a high-entropy ceramic fiber core layer that can withstand up to about 2000℃, which can improve the work safety of firefighters when performing tasks for a long time under extreme conditions;

[0031] 2. The filling sponge is soft and highly deformable, which can perfectly match different action scenes and ensure the wearing comfort of firefighters;

[0032] 3. No need for high-temperature calcination, the high-entropy ceramic fiber membrane can be formed at 400°C, and the subsequent hot pressing temperature of the alumina-high-entropy ceramic-alumina sandwich structure does not exceed 400°C, making the preparation process energy-saving and convenient.

[0033] In summary, it has both long-term fireproof and heat-insulating properties and deformability, ensuring the safety and comfort of firefighters during their work.

[0034] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a flowchart of a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge of the present invention;

[0036] Figure 2 A schematic diagram of the structure of an alumina fiber surface layer-high entropy ceramic nanofiber core layer-alumina fiber surface layer foam material prepared by a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge of the present invention;

[0037] Figure 3 This is a refractory burning test diagram of the alumina-high entropy ceramic filled sponge described in the test example of the present invention.

[0038] Among them: 1. Alumina fiber surface layer; 2. High entropy ceramic nanofiber core layer. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention clearer, the embodiments of the present invention are further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. Examples of the embodiments are shown in the accompanying drawings, where the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions.

[0040] It should be noted that the terms "include", "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or server comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or devices.

[0041] Like reference numerals and letters denote similar items in the following drawings, and thus, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0042] The present invention is designed taking into account the long-term fireproof and heat-insulating performance and wearing comfort of the fire-fighting suit: Figure 1 and Figure 2 As shown, a method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge comprises the following steps:

[0043] S1, preparing a high entropy ceramic nanofiber core layer;

[0044] S11, preparing a precursor sol containing a polymer template, a metal source and a solvent A by a sol-gel method;

[0045] In step S11, the polymer template is one of polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, polyacrylonitrile and any combination thereof; the metal source is one of ferric acetate, cobalt acetate, nickel acetate, copper acetate, zinc acetate, manganese acetate and any combination thereof; solvent A is one of ethanol, N,N-dimethylformamide, methanol and any combination thereof; the weight ratio of the polymer template to solvent A is 1:2 to 1:30, and the total metal content accounts for 1:5 to 1:30 of solvent A.

[0046] S12, performing electrostatic spinning on the precursor sol to obtain a precursor nanofiber membrane;

[0047] S13, heating the precursor nanofiber membrane, and then calcining it in an air atmosphere to obtain a high entropy ceramic nanofiber core layer;

[0048] In step S13, heating is performed in a vacuum oven at 200°C for 2 hours, the calcination temperature is 400°C-1000°C, and the heating rate is 2°C / min-10°C / min.

[0049] S2, preparing an inorganic mixed spinning solution or an organic mixed spinning solution containing an aluminum source, a solvent B and a spinning aid;

[0050] In step S2, the aluminum source is one of aluminum nitrate nonahydrate, aluminum chloride hexahydrate, aluminum acetate, aluminum sulfate, aluminum isopropoxide, trimethoxyaluminum, aluminum triethanol, tri-n-propoxyaluminum, aluminum n-butoxide, aluminum sec-butoxide, and aluminum tert-butoxide, and any combination thereof; the solvent B is one of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, n-pentanol, ethylene glycol, butanediol, hexanediol, or glycerol, and any combination thereof; the spinning aid is one of polyacrylamide, polyvinyl pyrrolidone, hydrolyzed polyacrylamide, polyacrylic acid and its salt, polyvinyl alcohol, and polyethylene oxide, and any combination thereof; the ratio of the aluminum source, the solvent B, and the spinning aid is 10-30:50-130:0.5-5.

[0051] S3, using an electrospinning process based on an inorganic mixed spinning solution or an organic mixed spinning solution, spinning an alumina fiber surface layer on both sides of the high entropy ceramic nanofiber core layer to obtain an alumina fiber surface layer 1-high entropy ceramic nanofiber core layer 2-alumina fiber surface layer 1 foam material having a sandwich structure;

[0052] S4. Hot-pressing the alumina fiber surface layer 1-high entropy ceramic nanofiber core layer 2-alumina fiber surface layer 1 foam material to obtain an alumina-high entropy ceramic filled sponge.

[0053] In step S4, the hot pressing temperature is 20°C-400°C, the time is 1 min-20 min, and the pressure is 1 kPa-1000 kPa.

[0054] The alumina-high entropy ceramic filling sponge is prepared by the method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filling sponge.

[0055] The application of the alumina-high entropy ceramic filled sponge in firefighting clothing.

[0056] Test example

[0057] like Figure 3 As shown, the alumina-high entropy ceramic filled sponge described in the present invention was calcined at a high temperature of 700°C without burning, which confirms the effectiveness of the present invention.

[0058] Therefore, the present invention adopts the above-mentioned long-term fireproof and heat-insulating alumina-high entropy ceramic filling sponge preparation method, alumina-high entropy ceramic filling sponge and its application, combining the flexibility of alumina fiber and the ultra-high temperature resistance of high entropy ceramic fiber to take into account the work safety and wearing comfort of fire suits. According to tests, the alumina-high entropy ceramic filling sponge can withstand a high temperature of 700°C without burning when used in fire suits.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge, characterized in that: The following steps are involved: S1, preparing a high entropy ceramic nanofiber core layer; S11, preparing a precursor sol containing a polymer template, a metal source and a solvent A by a sol-gel method; S12, performing electrostatic spinning on the precursor sol to obtain a precursor nanofiber membrane; S13, heating the precursor nanofiber membrane, and calcining it in an air atmosphere to obtain a high entropy ceramic nanofiber core layer; S2, preparing an inorganic mixed spinning solution or an organic mixed spinning solution containing an aluminum source, a solvent B and a spinning aid; S3, using an electrospinning process based on an inorganic mixed spinning solution or an organic mixed spinning solution, spinning an alumina fiber surface layer on both sides of the high entropy ceramic nanofiber core layer to obtain an alumina fiber surface layer-high entropy ceramic nanofiber core layer-alumina fiber surface layer foam material having a sandwich structure; S4. Hot-pressing the alumina fiber surface layer-high entropy ceramic nanofiber core layer-alumina fiber surface layer foam material to obtain an alumina-high entropy ceramic filled sponge.

2. The method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge according to claim 1, characterized in that: In step S11, the polymer template is one of polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, polyacrylonitrile and any combination thereof; The metal source is one of ferric acetate, cobalt acetate, nickel acetate, copper acetate, zinc acetate, manganese acetate, and any combination thereof; Solvent A is one of ethanol, N,N-dimethylformamide, methanol, or any combination thereof; The weight ratio of the polymer template to the solvent A is 1:2 to 1:30, and the ratio of the total metal content to the solvent A is 1:5 to 1:

30.

3. The method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge according to claim 1, characterized in that: In step S13, heating is performed in a vacuum oven at 200°C for 2 hours, the calcination temperature is 400°C-1000°C, and the heating rate is 2°C / min-10°C / min.

4. The method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge according to claim 1, characterized in that: In step S2, the aluminum source is one of aluminum nitrate nonahydrate, aluminum chloride hexahydrate, aluminum acetate, aluminum sulfate, aluminum isopropoxide, aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum n-butoxide, aluminum sec-butoxide, aluminum tert-butoxide, and any combination thereof; Solvent B is one of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, n-pentanol, ethylene glycol, butanediol, hexanediol or glycerol, or any combination thereof; The spinning aid is one of polyacrylamide, polyvinyl pyrrolidone, hydrolyzed polyacrylamide, polyacrylic acid and its salt, polyvinyl alcohol, polyoxyethylene and any combination thereof; The ratio of aluminum source, solvent B and spinning aid is 10-30:50-130:0.5-5.

5. The method for preparing the long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge according to claim 1, characterized in that: In step S4, the hot pressing temperature is 20°C-400°C, the time is 1 min-20 min, and the pressure is 1 kPa-1000 kPa.

6. Alumina-high entropy ceramic filled sponge prepared by the method for preparing a long-term fireproof and heat-insulating alumina-high entropy ceramic filled sponge as described in any one of claims 1 to 5.

7. Use of the alumina-high entropy ceramic filled sponge as described in claim 6 in firefighting clothing.